Strategies for leveraging media to improve leadership within nonprofits. (9th October 2021) - Scranton, Annie Pace
Abstract : When thinking about media exposure in the nonprofit world, more times than not, the end goal is to raise awareness to attract potential donors. We've seen this strategy work time and time again. In fact, one of our nonprofit clients, Concern Worldwide US, saw a 1 million donation come in after its CEO gave an appearance on Bloomberg television.